Memorandum of Understanding between the BRAC University, Mohakhali, Dhaka and BRAC Agriculture Research and Development Centre, Joydevpur, Gazipur (2010) - BRAC University; BRAC Agricultural Research and Development Centre (BRAC University and Bangladesh Agricultural Research and Development Centre, 2013)
1. Parties- (a) BRAC University and (b) BRAC Agricultural Research and Development Centre. 2. Background. 3. Roles and Responsibilities.